Avaliação descritiva e letramento matemático: uma proposta de intervenção pedagógica para o 9º ano do ensino fundamental de uma escola da rede municipal de Uruguaiana/RS - Vargas, Patricia Vasconcelos de (2023)
The present work is justified by the possibility of outlining alternative paths for the act of evaluating, which are significant and can support reflections and relevant discussions about this topic. This research was based on the theoretical framework of authors who are a reference in evaluation in a general context of education: Libâneo, Luckesi, Hadji, Haydt, among others. The proposal's main objective is to analyze the contributions of descriptive assessment in the development of mathematical literacy in 9th grade students. This investigation presents an exploratory and qualitative approach, implemented through a Pedagogical Intervention. This type of research is composed of two methods: the intervention method itself, which concerns the teaching method, and which in this study involved the elaboration, validation and implementation of a didactic proposal focused on evaluation; and the intervention evaluation method that involved the analysis, description and discussion of the collected information. Data referring to the intervention itself were collected through the transcription of the evaluators' speeches in the intervention validation process and the teacher/researcher's field diary. The instruments used in the analysis and collection of data from the evaluation of the intervention, on the other hand, come from productions written by 15 students from a school in the municipal network. The results of the first stage revealed the importance of an organized and coherent planning with instruments and evaluation criteria. The notes made by the evaluators in the process of validation of the intervention served to adjust its planning, allowing the proposal and its consequences to reach its objectives. The sequence of activities provided a gradual change in the students' cognitive and social behavior, especially with regard to participation and oral and written expression. The data collected from the students' productions were analyzed and interpreted through Discursive Textual Analysis, emerging three categories of analysis: Students' understanding in relation to school evaluation, Descriptive evaluation as a proposal for the development of mathematical literacy and The perspective of the subjects after the intervention. According to the result of the analysis, it is possible to infer that the procedural, dialogic and descriptive evaluation thought and developed in this study, contributed to the monitoring of the students' trajectory, helping to redefine the teacher's teaching method in order to promote important and necessary learning for this teaching stage.